Chronic epididymitis due to Chlamydia trachomatis LGV-L2 in an HIV-negative heterosexual patient: a case report - Daniela Andrea Paira; Daniela Andrea Paira; José Javier Olmedo; Carolina Olivera; Carolina Olivera; Andrea Daniela Tissera; Rosa Isabel Molina; Virginia Elena Rivero; Virginia Elena Rivero; Rubén Darío Motrich; Rubén Darío Motrich; Héctor Alex Saka; et al. (Frontiers Media S.A., 2023)
Chlamydia trachomatis is an obligate intracellular pathogen and the leading bacterial cause of sexually transmitted infections worldwide. Chlamydia trachomatis genovars L1-L3 are responsible for lymphogranuloma venereum (LGV), an invasive sexually transmitted disease endemic in tropical and subtropical regions of Africa, South America, the Caribbean, India and South East Asia. The typical signs and symptoms of C. trachomatis LGV urogenital infections in men include herpetiform ulcers, inguinal buboes, and/or lymphadenopathies. Since 2003, endemic cases of proctitis and proctocolitis caused by C. trachomatis LGV emerged in Europe, mainly in HIV-positive men who have sex with men (MSM). Scarce data have been reported about unusual clinical presentations of C. trachomatis LGV urogenital infections. Herein, we report a case of a 36-year-old heterosexual, HIV-negative male declaring he did not have sex with men or trans women, who presented to the Urology and Andrology outpatient clinic of a healthcare center from Cordoba, Argentina, with intermittent testicular pain over the preceding 6 months. Doppler ultrasound indicated right epididymitis and funiculitis. Out of 17 sexually transmitted infections (STIs) investigated, a positive result was obtained only for C. trachomatis. Also, semen analysis revealed oligoasthenozoospermia, reduced sperm viability as well as increased sperm DNA fragmentation and necrosis, together with augmented reactive oxygen species (ROS) levels and the presence of anti-sperm IgG autoantibodies. In this context, doxycycline 100 mg/12 h for 45 days was prescribed. A post-treatment control documented microbiological cure along with resolution of clinical signs and symptoms and improved semen quality. Strikingly, sequencing of the ompA gene revealed C. trachomatis LGV L2 as the causative uropathogen. Remarkably, the patient did not present the typical signs and symptoms of LGV. Instead, the infection associated with chronic testicular pain, semen inflammation and markedly reduced sperm quality. To our knowledge, this is the first reported evidence of chronic epididymitis due to C. trachomatis LGV L2 infection in an HIV-negative heterosexual man. These findings constitute important and valuable information for researchers and practitioners and highlight that C. trachomatis LGV-L2 should be considered as putative etiologic agent of chronic epididymitis, even in the absence of the typical LGV signs and symptoms.